CHANGES OF SOME SOIL PHYSICAL AND HYDROPHYSICAL CHARACTERISTICS IN RESPONSE TO DIFFERENT SPRINKLER TYPES AND NOZZLE SIZES - Walaa El-Shalakany; M.O El-Zakaziky; A.M. El-Araby; E.A. El-Sahhar; Y.E Arafa (Arab Universities Journal of Agricultural Sciences, 2009)
Soil characteristics' degradation had been considered as one of the most important problems that face the agricultural development processes under arid and semi-arid conditions due to non-suitability of the applied technologies and techniques, attributed to management considerations. Consequently, higher crop yield and quality reduction had been occurred due to the degradation of the plant healthy media (soil). Therefore, the goal of this investigation was to monitor the change detection of some soil physical and hydrophysical characteristics under sprinkler irrigated agriculture. However, the terminal objectives were to evaluate and monitor some soil characteristics changes (soil bulk density, hydraulic conductivity and soil penetration resistance) under different mode of action of sprinkler types (rotating and impact sprinkler) and corresponding nozzle sizes (small and large sizes). Hereby, field experiments were carried out for two seasons (2006 and 2007) in the Desert Experimental Farm of Faculty of Agriculture, AinShamsUniversity which is located at El-Bustan region, Behaira Governorate. Results revealed that soil characteristics were highly affected with the sprinkler mode of action and corresponding nozzle sizes. However, a power function proportion of soil penetration resistance with respect to applied rotating and impact sprinkler types and corresponding small and large nozzle sizes, had been observed and analyzed. Therefore, data analysis speculated that, selection of the appropriate sprinkler types under diverse field conditions and situations such as: crop type and design criteria of sprinkler irrigation systems, have to be considered for good agricultural development processes under Egyptian newly reclaimed regions.